Yakammaoto inhibits enterovirus 71 infection by reducing viral attachment, internalization, replication, and translation. Issue 6 (7th May 2015) - Yeh, Chia‐Feng; Wang, Kuo‐Chih; Lu, Chi‐Yu; Chiang, Lien‐Chai; Shieh, Den‐En; Yen, Ming‐Hong; Chang, Jung‐San
Abstract: Enterovirus 71 (EV71) can cause central nervous system infections with mortality and neurologic sequelae. At present, there is no effective therapeutic modality for EV71 infection. The infection is more common in families with poor socioeconomic status. Therefore, finding a readily available, cost‐effective therapeutic modality would be very helpful to these socioeconomically disadvantaged families. Yakammaoto is a cheap and readily available traditional prescription that is proven to have antiviral activity against coxsackievirus B4 (CVB4). CVB4 and EV71 are enteroviruses. In this study, we evaluated the antiviral activity of hot water extract of yakammaoto against EV71. The results of plaque reduction assay and flow cytometry demonstrated that yakammaoto dose dependently inhibited EV71 infection. In addition, reverse transcription‐polymerase chain reaction (RT‐PCR) and quantitative RT‐PCR results showed that yakammaoto reduced viral replication. Western blotting analysis showed that yakammaoto can inhibit viral protein production. Thus, our results suggest that yakammaoto should be considered to manage EV71 infection in the future.